VERIFICATION OF THE CRIME INFORMATION AS THE INITIAL STAGE OF CRIMINAL COURT PROCEDURE - L. R. Komarova (Russian Journal of Economics and Law)
Objective: to determine the nature and functional purpose of the preliminary investigation in the structure of criminal proceedings. Methods: dialectical, formal logical, comparative analysis. Results: basing on the analysis of norms of the Criminal-Procedural Code of the Russian Federation which include preliminary investigation in the list of activities for verification of a crime report, the necessity is proved to promote the structure of pre-court procedure. Proposition is made to include the pre-court verification into the sysem of criminal procedure. Special attention is paid to the analysis of features which determine the place of verification activity in the system of the stages of criminal proceedings in Russia. The most topical problems of the preliminary stage of the proceedings are shown, which have recently become the subject of sharp discussions. Scientific novelty: preliminary examination is considered on a new level as a stage preceding the criminal procedure. The content of the new stage is revealed, its place in the structure of criminal court procedure is defined. The importance to extinguish the preliminary examination into a special stage is theoretically proved. Practical value: the possibility to improve the structure of pre-court proceedings, by strengthening the initial stage of investigation. The conclusion about the functional expediency of existence of the pre-investigation verification allows to determine the main directions of modernization of criminal-procedural legislation.